2015
DOI: 10.1097/md.0000000000001884
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between CASC8, SMAD7 Polymorphisms and the Susceptibility to Colorectal Cancer

Abstract: Genome-wide association studies (GWASs) and a number of case–control studies have suggested that several single nucleotide polymorphisms (SNPs), rs7837328, rs7014346, rs6983267, rs10505477 on CASC8 gene and rs4939827, rs4464148, rs12953717 on SMAD7 gene are significantly correlated with the susceptibility to colorectal cancer (CRC). For the sake of clarifying the association, a meta-analysis was conducted and population heterogeneity was considered in the study.A total of 34 articles including 90 studies (168,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 67 publications
0
23
1
Order By: Relevance
“…Studies have shown that SNPs in lncRNAs may affect the biological processes of messenger RNA conformation, and results in the modification of its interacting partners. Interestingly, various cancer types, including CRC, prostate, breast and gastric cancer, have been reported in association with CASC8, (Lemire et al 2015;Yao et al 2015) possibly through its function as a lncRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that SNPs in lncRNAs may affect the biological processes of messenger RNA conformation, and results in the modification of its interacting partners. Interestingly, various cancer types, including CRC, prostate, breast and gastric cancer, have been reported in association with CASC8, (Lemire et al 2015;Yao et al 2015) possibly through its function as a lncRNA.…”
Section: Discussionmentioning
confidence: 99%
“…They discovered that the rs7837328 and rs6983267 SNPs of the CASC8 gene were linked with an increased risk of CRC in both Caucasian and Asian patients. SNPs of rs7014346 and rs10505477 also correlated with an increased risk of CRC but only in Caucasians [3].…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 99%
“…On the other hand rs4939827 and rs4464148 SNPs correlated with an increased risk of CRC only in Caucasians [3].…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 99%
See 2 more Smart Citations